Influence of 7T GRE-MRI Signal Compartment Model Choice on Tissue Parameters - Thapaliya, Kiran; Vegh, Viktor; Bollmann, Steffen; Barth, Markus (Frontiers in Neuroscience, 2020)
Quantitative assessment of tissue microstructure is important in studying human brain diseases and disorders. Ultra-high field magnetic resonance imaging data obtained using a multi-echo gradient echo sequence has been shown to contain information on myelin, axonal and extracellular compartments in tissue. Quantitative assessment of water fraction, relaxation time (T2*), and frequency shift using multi-compartment models have been shown to be useful in studying white matter properties via specific tissue parameters. It remains unclear how tissue parameters vary with model selection based on 7T multiple echo time gradient-recalled echo MRI data. We applied existing signal compartment models to the corpus callosum and investigated whether a three compartment model can be reduced to two compartments and still resolve white matter parameters (i.e. myelin water fraction and g-ratio). We show that myelin water fraction should be computed using a three compartment model in the corpus callosum, and the g-ratios obtained using three compartment models are consistent with previous reports. We provide results for other parameters, such as signal compartment frequency shifts.